2017
DOI: 10.1002/etc.3897
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends and flow dynamics of glyphosate and other pesticides within an agricultural watershed in Argentina

Abstract: In the present study, we evaluated the spatial and temporal trends of current-use pesticides in surface water and sediments as well as their relationship with hydrological stream dynamics within the agricultural watershed of El Crespo stream (Buenos Aires Province, Argentina). We sampled 2 contrasting sites: site 1 (upstream), surrounded by agricultural lands, and site 2 (downstream), surrounded by natural grasslands. Most of the applied pesticides (glyphosate, 2,4-D, atrazine, tebuconazole, and imidacloprid) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(30 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…In autumn/winter season, only two pesticides were found at 100% of the sites monitored (2,4-D and carbendazim), but all 20 compounds were quantified in biofilms with frequency ranging from 22% (thifensulfuron-methyl) to 83% (atrazine and tebuconazole, Table 2). Some spring and early summer rainfall events (Pascual Aguilar et al 2017;Pérez et al 2017;Rabiet et al 2010); the 230 same was observed in biofilms in the present study.…”
Section: Occurrence and Concentrationsupporting
confidence: 85%
“…In autumn/winter season, only two pesticides were found at 100% of the sites monitored (2,4-D and carbendazim), but all 20 compounds were quantified in biofilms with frequency ranging from 22% (thifensulfuron-methyl) to 83% (atrazine and tebuconazole, Table 2). Some spring and early summer rainfall events (Pascual Aguilar et al 2017;Pérez et al 2017;Rabiet et al 2010); the 230 same was observed in biofilms in the present study.…”
Section: Occurrence and Concentrationsupporting
confidence: 85%
“…Current-use pesticides are frequently detected in streams globally, often occur as complex mixtures, and can pose risks to aquatic life (Bereswill et al, 2013;Gilliom et al, 2006;Hageman et al, 2019;Hladik and Kolpin, 2016;Metcalfe et al, 2016;Nowell et al, 2018;Pérez et al, 2017;Stehle and Schulz, 2015;Stone et al, 2014). Shortterm peaks in pesticide concentrations in streams can occur as a result of seasonal or event-driven pesticide applications (e.g., infestation or public-health hazard) and streamflow conditions (Liess et al, 1999;Rabiet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides enter the riverine system either as particle bound, if the substances are sorbed to the topsoil and eroded and transported via surface-runoff, dissolved via drainage and the groundwater, or directly via spray-drift (Schulz 2004;Topaz et al 2018). The transport pathways for the particle bound or dissolved transport depend on the physicochemical properties of the substances, time of pesticide application, and the characteristics of the catchment (e.g., soils, land management) (Larson et al 1995;Pérez et al 2017). Once, entered the stream, the pesticide load dynamics is affected by the partitioning between the dissolved and the adsorbed phases, whereby some pesticides tend to bind to the suspended sediments and are transported as particulatebound pollutants, whereas others are more stable in their dissolved phase (Chapman et al 2013;Birch et al 2015;Carpenter et al 2016).…”
Section: Introductionmentioning
confidence: 99%